2019
DOI: 10.12659/ajcr.918569
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Recurrence in Prostate Cancer and Temporal Association to Bone Metastasis

Abstract: Objective: Rare presentation Background: Prostate cancer is a common cancer in men. Radical prostatectomy, i.e., the surgical removal of the entire prostate, is a frequently used option. Biochemical recurrence (BCR), i.e., detectable prostate specific antigen (PSA), is common in some men following such treatment. The timing of BCR to metastatic spread of disease in bones is usually a few years. If the biochemical failure occurs after a longer duration from the time of curative intent, it is generally believed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Prostate cancer (PCa) is the most commonly diagnosed cancer for males in 105 countries including North and South America, Western Europe and Australia [ 1 ]. The majority of PCa cases are localized disease with very high survival rate after initial treatment (∼100% 5-year survival), but recurrence may occur in about 40% as biochemical recurrence (BCR) or distant metastasis that has a significantly poorer prognosis (∼30% 5-year survival) [ 2 ]. Additionally, some may progress as castration-resistant prostate cancer (CRPC) or develop chemoresistance [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Prostate cancer (PCa) is the most commonly diagnosed cancer for males in 105 countries including North and South America, Western Europe and Australia [ 1 ]. The majority of PCa cases are localized disease with very high survival rate after initial treatment (∼100% 5-year survival), but recurrence may occur in about 40% as biochemical recurrence (BCR) or distant metastasis that has a significantly poorer prognosis (∼30% 5-year survival) [ 2 ]. Additionally, some may progress as castration-resistant prostate cancer (CRPC) or develop chemoresistance [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cranial neurological deficits or nerve palsies caused by prostatic cancer metastasis are uncommon in advanced disease but constitute important clinical characteristics. Skull metastasis can cause symptoms of nervous system debilitation, such as cranial nerve palsy, preferentially causing urological symptoms, facial nerve palsy, multiple cranial nerve palsies, otological symptoms, and ophthalmoplegia [ [2] , [3] , [4] , 14 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most skull bone metastases are purely intraosseous lesions limited to the calvarium or base of the skull [ 6 ]. A review of previous reports and literature revealed that metastatic prostate cancer of the temporal bone is rare, especially in the frontotemporal bone [ [1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] ].…”
Section: Introductionmentioning
confidence: 99%
“…Metastasis of a distant organ, typically bone or lymph nodes, is a typical consequence of BCR. The transition from BCR to metastasis may take a long period of time, extending over several years 14,15 . However, it has been shown that biochemical failure is not equal to clinical relapse 14 .…”
Section: Relapse After Radical Prostatectomymentioning
confidence: 99%
“…On the other hand, many viruses, such as mumps virus, HIV and HSV, 7,14 have been found to impair semen quality, and they may directly interact with spermatozoa or affect spermatogenesis by inducing local inflammation. [15][16][17] Previous studies found that SARS, 1 of the 3 epidemic coronaviruses to emerge in the past 20 years and that shows similar clinical presentations to COVID-19, 18 could cause orchitis 19 and focal testicular atrophy. 20 Considering the tens of millions of COVID-19 cases and that men are more vulnerable to COVID-19 than women, [21][22][23] it is imperative to determine the effect of COVID-19 on male reproduction.…”
Section: Introductionmentioning
confidence: 99%